Pushing through maximum depression to increase springboard dive height - Miller, D. I. (1998)
The results of the present study suggested that an effective pattern for board deflection incorporates a slowing followed by an increase in knee extension velocity allowing divers to push through maximum board depression. Seven of the 9 divers who scored 8.0 and above on the reverse dive pike employed this strategy.